Aktivitas antioksidan ekstrak etanol daun pecut kuda (Stachytarpheta jamaicensis (L.) Vahl) menggunakan metode ekstraksi berbasis gelombang ultrasonic - Rian Jumawardi; Agus Dwi Ananto; Rizqa Fersiyana Deccati (Universitas Mataram, 2021)
Free radical is an atom or molecule that has unpaired electrons, is reactive and unstable which can cause damage to cells and tissues. Secondary metabolite compounds in plants such as phenolics, flavonoids, tannins, and saponins can inhibit free radicals. One of the plants that has the potential as an antioxidant is a Stachytarpheta jamaicensis (L.) Vahl. The part of the plant that is often used as a medicinal ingredient by Indonesian people is the leaf part. The leaves of snakeweed are natural ingredients that are rich in phenolic compounds, flavonoids, tannins, and saponins. This study aims to determine the activity of free radical inhibition in the snakeweed leaf extract with Ultrasound Assisted Extraction method. Determination of free radical inhibition activity was examined using DPPH method at the concentration series of snakeweed leaf extracts of 60, 65, 70, 75, 80, and 85 ppm. The comparison solution used was vitamin C made with a concentration series of 4, 5, 6, 7, 9, and 11 ppm. The results showed that vitamin C had a free radical inhibitory activity with an IC50 value of 9.40 ± 0.07 ppm, while the extract of snakeweed leaf had free radical inhibition activity with an IC50 value of 74.32 ± 0.71 ppm. Based on the IC50 value, the intensity of free radical inhibition activity in vitamin C is classified as very strong and the extract of snakeweed leaf is strong